2020
DOI: 10.21203/rs.2.17846/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of type 2 diabetes mellitus and antidiabetic medication with risk of prostate cancer: a population-based case-control study.

Abstract: Background: Prostate cancer (PCa) and type 2 diabetes mellitus (T2DM) are prevalent conditions that often occur concomitantly. However, many aspects of the impact of T2DM, particularly the duration of T2DM and antidiabetic medications, on PCa risk are poorly understood. Methods: To assess the association of duration of T2DM and antidiabetic medication with PCa risk, we designed a matched case-control study, including 31,415 men with PCa and 154,812 PCa-free men in Prostate Cancer data Base Sweden (PCBaSe) 4… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This is compatible with the reported effect of insulin in the viability of PCa cells 40 . However, studies have been more focused on the effect of its use than on its duration, and they have yielded inconsistent findings with a meta-analysis declaring no association 41 , another indicating increased risk, 42 and recent original articles finding a protective relationship 13,19 . Time of exposure to antidiabetic agents may also be an additional source of heterogeneity 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is compatible with the reported effect of insulin in the viability of PCa cells 40 . However, studies have been more focused on the effect of its use than on its duration, and they have yielded inconsistent findings with a meta-analysis declaring no association 41 , another indicating increased risk, 42 and recent original articles finding a protective relationship 13,19 . Time of exposure to antidiabetic agents may also be an additional source of heterogeneity 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have not found differences by grade of disease [12][13][14] , whereas other authors have reported a higher risk of high-grade disease in patients with T2DM 15 . The most recent studies have found that lower rates in T2DM patients was limited to low/intermediate-grade PCa, with detection bias as a plausible explanation for this relationship [16][17][18][19] . However, none of these studies evaluated whether genetic susceptibility to PCa may play a modifying role in this complex association.…”
Section: Introductionmentioning
confidence: 99%